A Study on Quality of 12-Pulse Rectifier Source Feeding Three-Level T-NPC Inverter Under Switch-Open-Circuit Fault SVPWM Control: Published online: 31/10/2025 - Le, Nguyen Hong Phong; Pham, Dang Khoa; Van, Tan Luong; Nguyen, Duc Hieu; Nguyen, Van Nho (Journal of Technical Education Science, 2025)
This paper studies the quality of a 12-pulse diode rectifier source feeding a three-level T-NPC inverter working under a space vector PWM control for switch-open-circuit fault, denoted as SVPWM2. Before the occurence of the aforementioned fault, the inverter was working under conventional reduced common-mode voltage space vector PWM algorithm, denoted as SVPWM1 and providing the output voltage for a three-phase R-L load. The input and output currents of phase-shifting transformer, the input power factor of transformer, and the capacitor voltages at the DC-link are investigated. Simulation results show that the SVPWM2 method has the same characteristics as pre-fault space vector method (SVPWM1) in terms of total harmonic distortion of transformer primary and secondary currents, as well as input power factor. However, SVPWM2 has higher deviation in capacitor voltage compared to SVPWM1. Regarding to power losses, SVPWM2 has higher switching loss yet lower conduction loss than those of SVPWM1. The overall efficiency of SVPWM2 is slightly higher compared to that of SVPWM1.